Chronic Postthoracotomy Pain and Perioperative Ketamine Infusion. (1st June 2014) - Hu, Jie; Liao, Qin; Zhang, Fan; Tong, Jianbin; Ouyang, Wen
ABSTRACT The objectives of this study were to investigate whether continuous intravenous ketamine during the first 72 hours after thoracotomy could reduce the incidence and intensity of chronic postthoracotomy pain (CPTP) and to define the incidence and risk factors of CPTP. Seventy-eight patients receiving thoracotomy for lung tumor (benign or malignant) were randomly divided into two groups: ketamine group (n = 31) and control groups (n = 47). Patients in the ketamine group received intravenous ketamine 1 mg/kg before incision, followed by 2 μg/kg/minute infusion for 72 hours plus sufentanil patient-controlled intravenous analgesia after thoracotomy. Patients in the control group received intravenous a 0.9% normal saline and infusion plus sufentanil patient-controlled intravenous analgesia. The solutions patients received were blinded. The numerical rating scale (NRS) pain scores and the incidence and risk factors of CPTP were recorded during the first 6 months after surgery. Compared with control group, the incidence of chronic pain in the ketamine group did not decrease at 2 months (χ2 = 1.599, P = .206) and 6 months (χ2 = 0.368, P = .544) after surgery. Postoperative pain scores in the ketamine group were not significantly different from those of the control group patients at 2 months (U = 677.5, P = .593) and 6 months (U = 690.5, P = .680). The incidence of CPTP was 78.2% (61/78) at 2 months and 53.8% (42/78) at 6 months after surgery. Retractor used time (OR = 5.811, P = .002), inadequate acute pain control (NRS ≥ 5) (OR = 5.425, P = .048), and chemotherapy (OR = 3.784, P = .056) were independent risk factors for chronic postthoracotomy pain. The authors conclude that continuous intravenous ketamine (2 μg/kg/min) during the first 72 hours after thoracotomy was not beneficial to prevent chronic postthoracotomy pain. The independent risk factors for chronic postthoracotomy pain were retractor used time, inadequate acute pain control, and chemotherapy.